PERSEBARAN LOKASI PRAKTEK BIDAN MELALUI PENERAPAN SISTEM INFORMASI GEOGRAFIS MENGGUNAKAN METODE CLUSTERING - Setiawan, Andi; Nining, Sri; Laksana, Tri Ginanjar (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2017)
Distribution of midwife practice pomegranate (quality of service) in Cirebon is difficult to know where the location of the practice because of the vast area of Cirebon. Then, the number of pregnant women who are less get help quickly (giving birth without medical assistance) because of ignorance location midwife practice pomegranate (quality of service) nearby. And the number of midwives pomegranate (quality of service) has not cooperated with the insurance BPJS to perform payment transactions. This study uses a clustering method, which can segment data clustering method, which is used to facilitate information retrieval midwife pomegranate (quality of service). Clustering methods have representation stage pattern, the selection traits or characteristics, pattern proximity, distance measurement, data obtained from IBI (Indonesian Midwives Association) and the tools used: phpMyAdmin, notepad ++, xampp, GoogleMapApi, Dreamwaver. This system can be expected to map the location of the practice of midwives pomegranate (quality of service) in the district of Cirebon, can find the nearest location midwife pomegranate (quality of service), can find pomegranate midwives who work with BPJS to perform payment transactions. Then, hopefully it can help people in handling pregnant women rapidly. And, is expected to reduce maternal and child mortality.